EDUCAŢIA MUZICALĂ ÎN INSTITUŢIILE PREUNIVERSITARE - USM ADMIN (Moldova State University, 2009)
In this article, "Music Education" is mould to be a complex between the social phenomena and the cultural-spiritual human behaviors, a vital reality. There are examined and nominated the main objectives embraced by the Music Education. In the same time, are analyzed the most close adjacencies of the "Music Education" manifestation, an important one, the pupil physical and psychological abilities and vocations.